2021
DOI: 10.1038/s41467-021-21043-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumour heterogeneity and intercellular networks of nasopharyngeal carcinoma at single cell resolution

Abstract: The heterogeneous nature of tumour microenvironment (TME) underlying diverse treatment responses remains unclear in nasopharyngeal carcinoma (NPC). Here, we profile 176,447 cells from 10 NPC tumour-blood pairs, using single-cell transcriptome coupled with T cell receptor sequencing. Our analyses reveal 53 cell subtypes, including tumour-infiltrating CD8+ T, regulatory T (Treg), and dendritic cells (DCs), as well as malignant cells with different Epstein-Barr virus infection status. Trajectory analyses reveal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
173
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(191 citation statements)
references
References 78 publications
10
173
0
Order By: Relevance
“…cDCs expressing the SOCS2-centralized gene program could facilitate tumor immune surveillance ( 114 ). Clusters of IDO1 + cDCs and LAMP3 + cDCs are reported to repress the proliferation and function of effector T cells ( 115 , 116 ). DCs could also be restrained by regulatory T cells ( 117 ).…”
Section: Applications Of Scrna-seq In DC Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…cDCs expressing the SOCS2-centralized gene program could facilitate tumor immune surveillance ( 114 ). Clusters of IDO1 + cDCs and LAMP3 + cDCs are reported to repress the proliferation and function of effector T cells ( 115 , 116 ). DCs could also be restrained by regulatory T cells ( 117 ).…”
Section: Applications Of Scrna-seq In DC Studiesmentioning
confidence: 99%
“…In addition, a cluster of IDO1 + cDCs was identified in tumor environments and was predicted to impair T cell proliferation and cytotoxicity by promoting tryptophan depletion and kynurenine production ( 115 ). Interestingly, a cluster of tolerogenic and regulatory DCs, highly expressing migration (CCR7)- and maturation (LAMP3)-related genes, along with various chemokine ligands (CCL17, CCL19, and CCL22), was presumably able to interact with regulatory T cells and exhausted CD8 + T cells by binding to corresponding receptors in nasopharyngeal carcinoma at single-cell resolution ( 116 ). This immune-suppressive transcriptomic pattern in LAMP3 + DCs has been widely detected in various tumors by scRNA-seq, including in bladder urothelial carcinoma ( 128 ), hepatocellular carcinoma ( 129 , 130 ), and lung cancer ( 119 , 131 ), suggesting that universal crosstalk fosters an immune-suppressive niche for the tumor microenvironment.…”
Section: Applications Of Scrna-seq In DC Studiesmentioning
confidence: 99%
“…We reasoned that this bioinformatics challenge is theoretically possible with the EBV γ-herpesvirus genome given that it has been demonstrated for α-and β-herpesviruses [35][36][37]. Recent reports have demonstrated that scRNAseq alignment to EBV is possible in EBV-infected lymphoblastoid cell lines and NPC tumors [38][39][40], although alignment spanning the EBV genome has yet to be demonstrated. This is more likely to be observed in lytic-infected cells such as those in pseudo-ALI culture.…”
Section: Single Cell Rna-sequencing Reveals Cell Type-specific Ebv Transcriptional Profilesmentioning
confidence: 99%
“…Five subclusters of cells were identified from the GCTB lesion: C1_CD8 + T cells, C2_T cells, C3_T cells, C4_NK cells and C5_ CD8 + T cells ( Figures 5A, B ). C1_CD8 + T cells, and C2_CD8 + T cells shared specific T-cell markers genes, such as CD3D, CD3E, CD3G, CD8A, and CD8B ( 19 , 45 ). C2_T cells and C3_T cells expressed CD3D, CD3E, and CD3G.…”
Section: Resultsmentioning
confidence: 99%
“…Multiplex immunohistochemistry staining was performed according to the manufacturer’s instructions using the PANO 7-plex IHC kit (Panovue, Beijing, China) ( 19 , 20 ). Sections with a thickness of 3 μm were incubated overnight at 4°C with primary antibodies: anti-ACP5 (cat.…”
Section: Methodsmentioning
confidence: 99%